The Effect of the Use of Gadgets as a Learning Resource on Economic Learning Outcomes Reviewed from the Critical Thinking of Class X Students of SMAN 107 East Jakarta - Alifia Shafa Salsabila; Riswandi Riswandi; Aditya Pratama (Transpublika Publisher, 2026)
This study examined the influence of gadget utilization as a pedagogical resource and critical thinking on economic learning outcomes among 140 tenth-grade students at SMAN 107 East Jakarta. Grounded in the Unified Theory of Acceptance and Use of Technology (UTAUT), the research employed a quantitative survey design. Primary data were collected via closed-ended questionnaires, while secondary data were obtained from summative assessments. Path analysis using SPSS version 25 revealed four key findings: (1) gadget use directly and positively affected learning outcomes (coefficient = 0.345); (2) critical thinking directly and positively influenced learning outcomes (coefficient = 0.520); (3) gadget use directly and positively enhanced critical thinking (coefficient = 0.527); and (4) critical thinking significantly mediated the relationship between gadget utilization and learning outcomes, with an indirect effect of 0.274 (p < 0.05). These results affirm that integrating gadgets as learning tools, alongside fostering critical thinking skills, substantially improves student academic performance. The study underscores the importance of technology acceptance and cognitive development in educational settings, aligning with UTAUT’s emphasis on performance expectancy and facilitating conditions. Practical implications suggest that educators should strategically incorporate gadgets to promote higher-order thinking, thereby maximizing learning gains. Future research may explore additional mediating variables and broader sample populations to generalize these findings.